ANALISIS KINERJA KEUANGAN PADA CV. IMAN JAYA DI SAMARINDA - Fitriah, Siti Lailatul (EKONOMIA, 2012)
ABSTRACTGrowing economi activity, financial information is one of the indispensable requirement by the company to make appropriate polocies, much of the information needed by managers, one of which is the analysis of the financial performance of a company’s activities to determine the changers that occur in the financial statements and further investigate the company’s activities that occurred in order to obtain information. The financial statements can be measured by the ratio because of its practicality, this ratio include: Liquidity, Solvency, Profitability.Analysis tools used are:Lliquidity current ratio, acid test ratio, net working capital. Solvency: equity multiplier, debt to equity ratio, debt to asset ratio, Profitability: gross profit margin, net profit margin, return on assets.